Illustrations and studies in neotropical orchidaceae. the specklinia condylata group (pleurothallidinae) in Costa Rica and Panama - Bogarín, Diego; Serracín, Zuleika; Samudio, Zabdy (Lankesteriana: International Journal on Orchidology, 2014)
Taxonomy of discrete groups of taxa within Pleurothallidinae is critical for a better understanding of species diversity, evolution and phylogenetics. This paper focuses on the taxonomy and systematics of the species related to Specklinia condylata in Costa Rica and Panama. The taxonomic history and its phylogenetic position are discussed. The group is treated as comprising five species, three of them proposed as new to science. Each taxon is described on the basis of living material and illustrated in a composite plate. Overall distribution, maps, derivation of name, notes on species ecology, natural variation and diagnostic features are presented for each taxon. A key to the species and a comparative table is given to aid species identification.